2017
DOI: 10.1155/2017/7121485
|View full text |Cite
|
Sign up to set email alerts
|

Intranodal Palisaded Myofibroblastoma in a Submandibular Lymph Node

Abstract: Intranodal palisaded myofibroblastoma (IPM), also known as “intranodal hemorrhagic spindle cell tumor with amianthoid fibers,” is a rare benign mesenchymal tumor originating from smooth muscle cells and myofibroblasts, often with the presence of amianthoid fibers. Usually IPM affects inguinal lymph nodes, but three cases have been described in the submandibular and cervical lymph nodes. We report a new case of a 44-year-old women with submandibular mass. Cervical ultrasound showed a suspect right submandibular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…IPM usually presents as a painless, slow‐growing inguinal mass, which has been diagnosed in a wide age range (second to eighth decade). It is most commonly diagnosed in inguinal lymph nodes with rare cases reported in mediastinal, submandibular, and retroperitoneal lymph nodes . To our knowledge, our case is the first report of IPM in a para‐esophageal lymph node.…”
Section: Discussionmentioning
confidence: 69%
“…IPM usually presents as a painless, slow‐growing inguinal mass, which has been diagnosed in a wide age range (second to eighth decade). It is most commonly diagnosed in inguinal lymph nodes with rare cases reported in mediastinal, submandibular, and retroperitoneal lymph nodes . To our knowledge, our case is the first report of IPM in a para‐esophageal lymph node.…”
Section: Discussionmentioning
confidence: 69%
“…The most frequent location is the inguinal lymph nodes, 15 however, cervical, 16 submandibular, 5,15 axillar, 4 mediastinal, 10,17 and retroperitoneal 18 nodes have also been involved. Most cases affect men between the aged of 40 and 60 15 . Rahimi et al reported a pediatric case 19 .…”
Section: Discussionmentioning
confidence: 99%
“…IPM is a relatively rare intranodal mesenchymal tumor of smooth muscle fibers or myofibroblasts, typically presenting in the inguinal nodes and infrequently at other sites such as cervical [ 6 ], submandibular [ 7 , 8 ], supraclavicular [ 9 ], axillary [ 10 ], mediastinal [ 11 ], and retroperitoneal nodes [ 12 ]. Although mostly seen in middle-age, IPM can affect a broad age group (19–71 years) [ 10 ], with a single case reported in an infant [ 13 ].…”
Section: Discussionmentioning
confidence: 99%